2008
DOI: 10.1099/vir.0.2008/001081-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in virulence among porcine circovirus type 2 isolates are unrelated to cluster type 2a or 2b and prior infection provides heterologous protection

Abstract: Porcine circovirus type 2 (PCV2) is divided into two genetic clusters designated PCV2a and PCV2b. The objectives of this study were to determine whether isolates from different clusters vary in virulence and to determine whether infection with PCV2a isolates induces protective immunity against subsequent infection with a recent PCV2b isolate. One-hundred and thirteen conventional specific-pathogen-free (SPF) pigs were assigned randomly to treatment groups and rooms: pigs inoculated with PCV2a cluster isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
68
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 40 publications
5
68
2
2
Order By: Relevance
“…It was recently reported that the virulence of PCV2a and PCV2b did not differ in specific-pathogen-free (SPF) pigs [22]. However, we found that PCV2b can raise the mortality rate on conventional commercial farms infected with various pathogens such as PRRSV and M. hyopneumoniae.…”
Section: Discussioncontrasting
confidence: 41%
“…It was recently reported that the virulence of PCV2a and PCV2b did not differ in specific-pathogen-free (SPF) pigs [22]. However, we found that PCV2b can raise the mortality rate on conventional commercial farms infected with various pathogens such as PRRSV and M. hyopneumoniae.…”
Section: Discussioncontrasting
confidence: 41%
“…While differences in virulence between PCV2 isolates exist (Opriessnig et al, 2006), this appears not to be confined to genotype (Opriessnig et al, 2008). To our knowledge, this is the first study comparing apoptosis in pigs infected with PCV2a or PCV2b.…”
Section: Discussionmentioning
confidence: 90%
“…The current commercial vaccines are based on PCV2a genotype. Cross-protection between PCV2a and PCV2b genotypes is further supported by the efficacy of PCV2a-based vaccines under field conditions (5,24,27). However, PCV2-associated diseases (PCVAD) outbreaks in vaccinated herds do occur (25).…”
Section: Discussionmentioning
confidence: 96%